Green Lantern. Vol. 2, Love and war - Adams, Jeremy (Screenwriter); Marz, Ron; Humphries, Sam (DC Comics, 2025)
"The cosmos is thrown into chaos as strange new Lanterns with strange new powers begin to crop up, forcing Hal Jordan to the very edge! It's all out war in space as he teams with his fellow Lanterns to try and prevent the entire emotional spectrum from collapsing, but how far will he have to go to uphold his duties? And what about the unseen threat lurking just around the corner?"--